2006
DOI: 10.1038/sj.cdd.4401886
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated degradation of FADD and procaspase 8 in cells expressing human papilloma virus 16 E6 impairs TRAIL-mediated apoptosis

Abstract: Viruses have developed sophisticated strategies to evade host defenses and facilitate the production and spread of progeny. In this study, we show that transfection of the human papillomavirus (HPV) 16 E6 oncogene into HCT116 cells provides protection from tumor necrosis factor-related apoptosis inducing ligand (TRAIL)-mediated apoptosis. Additionally, we demonstrate that the protection provided by E6 is dose-dependent because higher levels of E6 provide greater protection. The mechanism underlying this protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 50 publications
5
85
0
Order By: Relevance
“…We identified that TNFa/ CHX-induced LMP is not an apoptosis initiating, but amplifying process downstream of MOMP, and it is triggered by mitochondrial ROS generated as the result of a caspase-3-mediated cleavage of the p75 NDUFS1 subunit of complex I. A similar finding was obtained in two different cellular systems, MEFs and HeLa cells, although molecular tools for manipulating p75 levels were not available for MEFs, and HeLa cells were less sensitive to TNFa/CHX-induced apoptosis due to the expression of HPV E6 and E7 genes (Garnett et al, 2006;Filippova et al, 2002). The mitochondrial production of ROS by TNFa has been shown in previous reports, and it was also suggested that these ROS somehow contribute to the apoptotic or necrotic process (Kim et al, 2010;Lin et al, 2004;Shoji et la., 1995;Schulze et la., 1993;Shen and Pervaiz, 2006).…”
Section: Discussionsupporting
confidence: 58%
“…We identified that TNFa/ CHX-induced LMP is not an apoptosis initiating, but amplifying process downstream of MOMP, and it is triggered by mitochondrial ROS generated as the result of a caspase-3-mediated cleavage of the p75 NDUFS1 subunit of complex I. A similar finding was obtained in two different cellular systems, MEFs and HeLa cells, although molecular tools for manipulating p75 levels were not available for MEFs, and HeLa cells were less sensitive to TNFa/CHX-induced apoptosis due to the expression of HPV E6 and E7 genes (Garnett et al, 2006;Filippova et al, 2002). The mitochondrial production of ROS by TNFa has been shown in previous reports, and it was also suggested that these ROS somehow contribute to the apoptotic or necrotic process (Kim et al, 2010;Lin et al, 2004;Shoji et la., 1995;Schulze et la., 1993;Shen and Pervaiz, 2006).…”
Section: Discussionsupporting
confidence: 58%
“…In addition to the TNF pathway, E6 is capable of inhibiting apoptosis stimulated by both Fas and TRAIL pathways. This inhibition is mediated by E6 binding to and degradation of both the FADD adapter protein and the effector caspase-8 (Garnett et al, 2006). As the binding of FADD is not dependent on the conserved PDZ domain of high-risk E6, but rather by a new domain (Tungteakkhun et al, 2008), it is possible that other E6 proteins may inhibit these extrinsic pathways.…”
Section: The Role Of the E6 Proteinmentioning
confidence: 99%
“…Moreover, HPV infected cells avoid this process of cell death by E6-mediated inactivation of p53. This oncogene interferes with other pro-apoptotic proteins of both extrinsic and intrinsic apoptotic pathways, such as Bak, FADD and pro-caspase 8 (Garnett et al, 2006;Narisawa-saito & Kiyono, 2007;Thomas & Bank, 1999). Thus, these two oncoproteins are essential factors for HPV-induced cellular immortalization, transformation and carcinogenesis.…”
Section: Life Cycle Of the Human Papillomaviruses And Molecular Mechamentioning
confidence: 99%
“…E6 is involved in the blockage of apoptosis acting in both major apoptotic pathways: a. the extrinsic pathway, which triggers extracellular signals that induce the activation of "death receptors" on the cell surface: 1) E6 binds to the death receptor TNFR-1, inhibiting TNFR-1 association with the TRADD (TNFR1-associated death domain adapter molecule) and blocking TNFR-1 death domain mediated apoptosis [47]; 2) E6 inhibits apoptosis by binding and degrading both the FADD adapter protein and caspase-8 [53].…”
Section: E6 Hpvmentioning
confidence: 99%
“…Although HPVs 26,53, and 66 are probably high-risk types limited data link them to cervix cancer [3]. HPV16 accounts for near 60% of the cervical cancer cases in most countries, followed by HPV-18, -31 and -45.…”
Section: Introductionmentioning
confidence: 99%